THE EFFECT OF USE OF CONCENTRATES BASED ON BROILER FARM WASTE IN RATIONS ON BODY WEIGHT LOSS AND DIGESTIVE ORGANS LANDRACE PIG - I N. T., ARIANA; WARMADEWI, D. A.; PUTRI, B. R. T.; MIWADA, I N. S. (Majalah Ilmiah Peternakan, 2022)
This research was conducted with the aim of knowing the effect of using protein concentrate based on broiler farm waste (KPLA) in rations on weight loss and digestive organ weight. The research used a completely randomi- zed design (CRD) with three treatments and four replications. The treatment is, A: with the use of 0% KPLA, B: with the use of 12% KPLA and C: with the use of 24% KPLA. The research used 12 pigs finisher phase with an average body weight of 66.6 ± 7.74 kg. The research parameters were body weight loss, small intestine weight and length, large intestine weight, and spleen weight. The results of the research were, after fasting for 12 hours, with the use of 0% and 12% KPLA there was a loss of body weight of 2.4% and 1.8% (P>0.05). The use of 24% KPLA (C) can increase body weight loss by 6.2%, significantly higher compared to A. The use of 0% - 12% KPLA does not cause a significant difference in the weight and length of the small intestine (P> 0.05), but with 24% KPLA (C) significan- tly reduced the weight of the small intestine by 11.9% and 11.3% in the length of the small intestine (P<0.05). The use of 0% - 24% KPLA did not affect the weight of the large intestine and the weight of the spleen (P>0.05). The conclusion of this research was the use of KPLA up to 12% did not cause significant changes in the parameters of slaughter weight, weight loss, weight and length of the small intestine. It is recommended to use KPLA in landrace pig rations up to 12%.